Beban Kerja Terhadap Stres Kerja Pada Karyawan : Hubungan beban kerja terhadap stres kerja - Yevika Equilera, Yevika Equilera; Nuzsep Almigo (IDEA: Jurnal Psikologi, 2025)
The work challenges experienced by employees, such as increased workload and time pressure, have an impact on the psychological and physiological conditions of employees, especially at Depot X. This phenomenon causes symptoms of job stress that can affect productivity and safety. This phenomenon causes symptoms of work stress that can affect productivity and work safety. This study aims to determine the relationship between workload and work stress in employees of depot X PT Y. This research method is quantitative with data collection using a workload scale questionnaire with work stress. The subjects in this study amounted to 105 people. The sampling technique used in this study is simple random sampling. The data analysis techniques used are validity and reliability tests. The data analysis method in this study has two stages, namely assumption / prerequisite testing and hypothesis testing. The results of research conducted on X PT Y depot employees using workload variables (independent variables) and work stress variables (dependent variables) show that these variables have a linear relationship with a value of F = 26.765 and P = 0.000. And the two variables have a relationship seen from the bivariate correlation test and get a value of P = 0.000. Based on the results obtained from data analysis and discussion, the researcher draws the conclusion that there is a relationship between workload and work stress in X PT Y depot employees.